Comparative study of combined co-enzyme Q10 and Clomiphene Citrate vs Clomiphene Citrate alone for ovulation induction in patients with polycystic ovarian syndrome - Hafsa Jamal; Khadija Waheed; Raana Mazhar; Muhammad Zeeshan Sarwar (Journal of the Pakistan Medical Association, 2023)
A total of 136 patients with PCOS were followed through the Department of the Obstetrics and Gynaecology, Unit-IV, Lady Aitchison Hospital, Lahore. Patients were randomly divided by lottery method into two groups i.e., Group-A (CoQ10 plus Clomiphene citrate) and Group-B (Clomiphene citrate alone). The selected patients in the study group (group-A) were given Clomiphene citrate 100mg/day from cycle days 2-6 for 45 days (2 cycles) and CoQ10 in a dose of 50mg soft gel capsules thrice per day starting at cycle day-2, until HCG administration. Patients in controlled group (group-B) received Clomiphene citrate 100mg/day twice a day cycle for 45 days. Data were analysed in SPSS v25.0. In group-A (CoQ10 plus Clomiphene citrate), successful ovulation induction was noted in 16 (23.5%) patients, showing that with the addition of CoQ10, the chances of ovulation induction increased. Keywords: Co-enzyme Q10, Clomiphene Citrate, Ovulation Induction, Polycystic Ovarian Syndrome.